Resveratrol Triggers Apoptosis In Colon Cancer Cells Rather Than Senescence - Madencioğlu, Servet; Becer, Eda; Kabadayı, Hilal; Vatansever, Hafize Seda; Yücecan, Sevinç (Progress in Nutrition, 2021)
Objective: Resveratrol is a phenolic compound that classified in stilbenoid and used as anticancer agent in many cancer types. The purpose of the study is to determine apoptotic and senescence inducing effects in primary (Colo-320) and metastatic (Colo-741) colon cancer cells.Methods: Cell growth and cytotoxicity were detected by MTT method in both Colo-320 and Colo-741 cell lines. Apoptotic and senescence inducing activities were tested with TUNEL staining, X-gal staining and immunocytochemistry using antibodies directed against to Bax, Bcl-2, caspase-3, Hsp27, Lamin B1, p16, cyclin B1.Results: According to MTT results, 25 μg/mL and 10 μg/mL concentrations of resveratrol were found more effective for Colo-320 and Colo-741 cell lines, respectively. As a result of immunocytochemical staining, Bax immunoreactivity was significantly increased while Bcl-2 immunoreactivity significantly decreased in Colo-320 cell line. Increased Hsp27, lamin B1 and p16 immunoreactivities on Colo-320 cells were not significant. In Colo-741 cells, Bcl-2 immunoreactivity was significantly increased. Hsp27 immunoreactivity in Colo-320 cell line was significantly higher than Colo-741 cell line. In addition, after resveratrol administration, while the TUNEL positive cells significantly increased in Colo-320 cells, X-gal positive cells was detected in Colo-741 than Colo-320 cells.Conclusion: Resveratrol can inhibit cell viability both in primer and metastatic colon cancer cells. However, resveratrol might be more effective triggering mitochondrial-mediated apoptosis in primary colon cancer cells. Apoptotic and cell cycle inhibiting effects of resveratrol may differ by cell type. Therefore, resveratrol may be a potential phytotherapeutic agent for colon cancer according to the cell origin.